PENGARUH PAPARAN SUHU TERHADAP KUALITAS SPERMATOZOA MENCIT JANTAN (MUS,MUSCULUS) STRAIN JEPANG - Ermiza Ermiza (SAINSTIS, 2012)
Spermatogenesis is a process of spermatozoa conception in tubulus seminiferus, which is influenced by various different factors, including hormonal, inhibit epididimis deterent, radiation and temperature. Conducive temperature in the regulation of spermatogenesis is below normal body temperature, which is 37°C. Maximum activity of most human enzim works within about 37°C, since temperature above 37°C will create denaturalization of enzim. Enzim is needed for cell metabolism. Exposure in high temperature resulted from a physical and psychological  stress  activates  central  and  peripheral  response  of  endoktrin system. Activating endoktrin system of hipotalamus-Hipofise-Adrenal involves neurohormon CRH, CRH to GnRH and disturbs activity of adenohipofise in producing FSH, LH which in turn disturbs spermatogenesis. The purpose of this research is to analyze the impact of the exposure in the temperature of 40°C upon quantity, mortility, and morphology of spermatozoa male mencit within one cicle of spermatogenesis. The research uses the method of Post Test Only Control Group Design conducted in April to October 2010 in Pharmachology Laboratorium of Medical Faculty of Unand Padang. The samples were taken from 24 male mencit of 2-3 months, with an avarage weight of 25-35 grams, divided into 4 groups, i.e. controlled group and 3 treated groups. The treatment was based on the lenght of exposure in the temperature of 40°C. This exposure lasts about 15, 30 and 45 minutes everyday in 36 days. The result is analyzed using Kolmogorof Smirnof Test,  data  from  normal  distribution  analyzed  with  Anova  Test,  if  result  is signifikan continued with Post-Hoc-Test (Bonferroni). If data from distribution is not normal analyzed with Kruskal Wallis. The   research   on   some   spermatozoa   using   Anova   test   indicates unsignificant relationship (p0,05) between controlled and treated group. However,   research   on   the   percentage   of   mortilitas   and   morphology   of spermatozoa shows significant differences (p0,05). Avarage decrease of amount, percentage of motility and morphology of abnormal spermatozoa is comparable to the time of exposure in the temperature of 40°C witih 36 days. Based on this research, it is safe to conclude that the exposure in 40°C gives a significant  impact  on  the  declining  quality  of    spermatozoa.  It  is  urged  that detailed researches should be conducted on the impact of exposure in high temperature upon the structure of spermatozoa moleculs, such as DNA, mitokondria and the level of tertosteron.